Struktur Linguistik Bahasa Sintaksis Dan Sematik - Dea Ayu Angraini; Alyada Ulya; Silvina Noviyanti (Departement of Mathematics Education, 2024)
This research aims to analyze the linguistic structure of a language, focusing on two main aspects: syntax and semantics. Syntax deals with the rules and patterns of sentence construction in a language, while semantics examines the meaning contained within the elements of the language. In this study, a descriptive method is used to thoroughly describe the relationship between sentence structure and its meaning. Data is collected through literature reviews and text analysis related to syntactic and semantic phenomena. The research results show a close relationship between syntactic structure and semantic interpretation in the process of language communication. A good understanding of these two aspects can enhance language skills and provide a more comprehensive linguistic analysis.